2009
DOI: 10.1002/lpor.200810052
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of slow‐light coupled‐resonator optical gyroscopes

Abstract: We investigate the connection between group velocity and rotation sensitivity in a number of resonant gyroscope designs. Two key comparisons are made. First, we compare two conventional sensors, namely a resonant fiber optic gyroscope (RFOG) and an interferometric fiber optic gyroscope (FOG). Second, we compare the RFOG to several recently proposed coupled-resonator optical waveguide (CROW) gyroscopes. We show that the relationship between loss and maximum rotation sensitivity is the same for both conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 23 publications
1
45
0
Order By: Relevance
“…It has also been theoretically and experimentally proved that the extreme dispersion of slow light can lead to an enhancement of the spectral sensitivity of interferometers [4,5]. The role of slow light in gyroscopes has also been theoretically investigated [6]. Recent works [7,8] have theoretically demonstrated that Beer-Lambert-Bouguer (BLB) absorption can be increased while light transmits through a special kind of microstructured photonic crystal (PC) cuvette.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been theoretically and experimentally proved that the extreme dispersion of slow light can lead to an enhancement of the spectral sensitivity of interferometers [4,5]. The role of slow light in gyroscopes has also been theoretically investigated [6]. Recent works [7,8] have theoretically demonstrated that Beer-Lambert-Bouguer (BLB) absorption can be increased while light transmits through a special kind of microstructured photonic crystal (PC) cuvette.…”
Section: Introductionmentioning
confidence: 99%
“…They are widely used as key components of inertial navigation systems in many industrial and military applications, such as airplanes, ships, satellites, and so on. Considerable research effort has been devoted to realizing chip-scale compact optical gyroscopes [4][5][6][7][8][9][10][11][12][13][14][15][16][17] because such small and navigation-grade rotation sensors have the potential to be used in mobile platforms and may extend into numerous applications. However, the sensitivity of an optical gyroscope decreases as the size of the sensing element decreases.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been theoretically and experimentally proved that the extreme dispersion of slow light can lead to an enhancement in the spectral sensitivity of interferometers given by n g [4]. The role of slow light in enhancing gyroscope performance [5] and Beer-Lambert-Bouguer (BLB) absorption [6,7] has also been theoretically and/or experimentally investigated. Generally speaking, light-matter interactions have been found to be only enhanced in structural slow light systems (e.g.…”
Section: Introductionmentioning
confidence: 99%